2010
DOI: 10.1007/s00432-010-0872-1
|View full text |Cite
|
Sign up to set email alerts
|

Thymidilate synthase expression predicts longer survival in patients with stage II colon cancer treated with 5-flurouracil independently of microsatellite instability

Abstract: This retrospective investigation suggests that TS gene expression at mRNA level can be a useful marker of better survival in patients (especially of those with cancers of stage II) receiving 5-FU adjuvant chemotherapy, independently of the MSI status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
4
13
1
Order By: Relevance
“…This finding is of particular interest as it again supports the concept that mixed carcinomas have a distinct molecular profile and possibly clinical behavior, and that molecular biomarkers might be predictive of the response to chemotherapy also in this group of neoplasms. In fact, referring to the knowledge available about colorectal cancer (which was the most prevalent location in our series), our data are in line with some previous studies on the unfavorable prognostic role of low TS gene expression in colon cancer patients, with special reference to those treated with antifolate drugs [24,25], even though at the same time our results are in sharp contrast to recent data on the adverse prognostic role of high TS protein expression in gastroenteropancreatic neuroendocrine neoplasms [16]. However, due to the limited number of cases, it was not possible to analyze the impact of TS gene expression levels on survival in a homogeneous group of chemotherapy-treated patients.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is of particular interest as it again supports the concept that mixed carcinomas have a distinct molecular profile and possibly clinical behavior, and that molecular biomarkers might be predictive of the response to chemotherapy also in this group of neoplasms. In fact, referring to the knowledge available about colorectal cancer (which was the most prevalent location in our series), our data are in line with some previous studies on the unfavorable prognostic role of low TS gene expression in colon cancer patients, with special reference to those treated with antifolate drugs [24,25], even though at the same time our results are in sharp contrast to recent data on the adverse prognostic role of high TS protein expression in gastroenteropancreatic neuroendocrine neoplasms [16]. However, due to the limited number of cases, it was not possible to analyze the impact of TS gene expression levels on survival in a homogeneous group of chemotherapy-treated patients.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the Cox hazard regression model revealed that only TP mRNA expression could predict the efficacy This finding is consistent with earlier findings that TP may be a prognostic marker in the adjuvant setting [29,34,35]. However, OPRT was not a prognostic factor in our study; this finding was inconsistent with previous findings [20].…”
Section: Discussionsupporting
confidence: 70%
“…For our study we selected as candidate molecular markers the colorectal cancer classifiers MMR system and CIMP, as well as the following single molecular markers: TP53 (p53), β-catenin (CTNNB1), BRAF c.1799 T > A (V600E) mutation and TYMS. The first three markers were chosen because they are involved in CRC tumorigenesis [30], whereas TYMS was analysed because it could be used to identify a subgroup of stage II colon cancer patients who better benefit from the use of adjuvant chemotherapy, as we pointed out in a previous study [31]. …”
Section: Introductionmentioning
confidence: 99%